2016
DOI: 10.1051/ocl/2016039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of technical management on the fatty-acid composition of high-oleic and high-linoleic sunflower cultivars

Abstract: -We investigated the effects of several crop management parameters on the fatty-acid composition of very high-oleic (VHO) and a very high-linoleic (VHL) sunflower cultivar. Experiments were performed on these varieties grown on field plots in 2009 and 2010. Yield and fatty-acid composition were determined and the effect of irrigation was investigated at the flowering stage in VHL cultivars. We also evaluated the effects of three sowing dates studied on Antonil, a VHL cultivar. Yield and fatty-acid content were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Monounsaturated fatty acids, however, increased markedly during the same period (Tables 2 and 3 (Chehade et al, 2016). In sunflower and safflower, a decrease in both oleic and palmitic acids was noticed during ripening (Gouzy et al, 2016;Roche et al, 2016;Merah et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Monounsaturated fatty acids, however, increased markedly during the same period (Tables 2 and 3 (Chehade et al, 2016). In sunflower and safflower, a decrease in both oleic and palmitic acids was noticed during ripening (Gouzy et al, 2016;Roche et al, 2016;Merah et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Delaying the sowing date induced a decrease of unsaturated fatty acids in our experiment. Environmental effects (temperature or water regimes) have already been described to impact significantly the seed composition of several oil crops [23][24][25]. More recently, the effect of intercepted solar radiation was reported.…”
Section: Effect Of Delaying Sowing Date On Fatty Acids Composition Inmentioning
confidence: 98%
“…Lindsey et al [34] have reported, in Arabidopsis mutants, that overexpressing SMT-2 results in higher accumulation of β-sitosterol highlighting the involvement of this enzyme in the regulation of sitosterol/campesterol balance. Through the activity of the SMT-2 enzyme, results on safflower indicated that it may be possible to modify the sterol and fatty acid contents and composition by cultural practices management [25,26]. In terms of the distribution of phytosterols in the seed, the stigmaterol was the only sterol that presented a higher concentration in the hull compared to the embryo.…”
Section: Sterols Content and Repartition In Safflower Seedsmentioning
confidence: 99%
“…Oil from HO sunflowers bearing Pervenets mutation shows a fatty acid profile characterized by 80–90% oleic acid, 1–10% linoleic acid and almost undetectable linolenic acid content (lower than 0.3%) (Table 1). Even for the highest oleic acid values, HO sunflower hybrids show no significant difference in grain yield, oil content, and seed productivity when compared to conventional sunflower hybrids (Angeloni et al, 2017; Carvalho et al, 2019; Fick, 1984; Gouzy et al, 2016; National Sunflower Association, 2018; Van der Merwe et al, 2013).…”
Section: Replacing Trans Fatty Acids (Tfa) In Food Processingmentioning
confidence: 99%